Outsourcing economics : global value chains in capitalist development - Milberg, William S., 1957-; Winkler, Deborah (Cambridge : Cambridge University Press, 2013)
Outsourcing Economics has a double meaning. First, it is a book about the economics of outsourcing. Second, it examines the way that economists have understood globalization as a pure market phenomenon, and as a result have 'outsourced' the explanation of world economic forces to other disciplines. Markets are embedded in a set of institutions - labor, government, corporate, civil society, and household - that mold the power asymmetries that influence the distribution of the gains from globalization. In this book, William Milberg and Deborah Winkler propose an institutional theory of trade and development starting with the growth of global value chains - international networks of production that have restructured the global economy and its governance over the past twenty-five years. They find that offshoring leads to greater economic insecurity in industrialized countries that lack institutions supporting workers. They also find that offshoring allows firms to reduce domestic investment and focus on finance and short-run stock movements.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Offshore outsourcing -- United States; Labor market -- United States; Foreign trade and employment -- United States; Globalization -- Economic aspects; Free trade -- United States